Comparing provision and appropriateness of health care between immigrants and non-immigrants in Germany using the example of neuraxial anaesthesia during labour: cross-sectional study. Issue 8 (21st August 2017) - Razum, Oliver; Reiss, Katharina; Breckenkamp, Jürgen; Kaufner, Lutz; Brenne, Silke; Bozorgmehr, Kayvan; Borde, Theda; David, Matthias
Abstract : Objective: Research on health services for immigrants has mostly been concerned with access barriers but rarely with appropriateness and responsiveness of care. We assessed whether appropriateness and responsiveness of care depend on migration status, using provision of neuraxial anaesthesia (NA) during labour as indicator. In relation to their migration status, we analysed whether (1) women undergoing elective or secondary/urgent secondary caesarean sections (ESCS) appropriately receive NA (instead of general anaesthesia), (2) women delivering vaginally appropriately receive NA and (3) women objecting to NA, for example, for religious reasons, may deliver vaginally without receiving NA (provider responsiveness). Design: Cross-sectional study. Setting: Three obstetric hospitals in Berlin, Germany. Methods: Questionnaire survey covering 6391 women with migration history (first and second generations) and non-immigrant women giving birth; data linkage with routine obstetric data. We assessed the effects of migrant status, German language proficiency, religion and education on the provision of NA (primary outcome) after adjusting for other maternal and obstetric parameters. Results: The chance of receiving NA for elective/ESCS was independent of migrant status after controlling for confounding variables (adjusted OR (aOR) 0.93, 95% CI 0.65 to 1.33). In vaginal deliveries, first (but not second) generation women (aOR 0.79, 95% CI 0.65 to 0.95), women with low German language skills (aOR 0.77, 95% CI 0.58 to 0.99) and women with low educational attainment (aOR 0.62, 95% CI 0.47 to 0.82) had lower chances of receiving NA; there was no evidence of overprovision among women with strong affinity to Islam (aOR 0.77, 95% CI 0.63 to 0.94). Conclusions: We found evidence for underprovision of care among first-generation immigrants, among women with low German language proficiency and particularly among all women with low educational attainment, irrespective of migration status. There was no evidence for overprovision of care to immigrant women, either inappropriately (general anaesthesia for ESCS) or because of low provider responsiveness (no opt-out for NA in vaginal delivery).